Designing Sustainable City: Feasibility of Gamification-Integrated STEM-Based Science Learning Tools - Anugrah Putri Nur'aini; Shelly Efwinda; Muhammad Amiq Zahidsyahtya; Erna Sari; Atin Nuryadin; Nurul Fitriyah Sulaeman (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2026)
– This study aims to develop and validate STEM-based learning tools integrated with Game-Based Learning themed "Sustainable City" to address the lack of student engagement in STEM education. Employing the Educational Design Research (EDR) method, this research focuses on the design and construction phase involving the development of student worksheets and teaching modules. The product feasibility was assessed by five experts through content and graphic validation using a 46-item instrument with a 4-point Likert scale. Data were analyzed using percentage analysis and Aiken’s V index. The results demonstrate that the content feasibility achieved an average score of 93% (Very Valid) with an Aiken’s V of 0.90, highlighting strong validity in integrating the EDP and SDGs. The graphic feasibility obtained an average score of 87% (Very Valid). However, the specific finding revealed a critical gap in the "Cover Design" indicator, which scored the lowest (75%). Overall, the STEM-EDP materials are declared academically feasible by experts, although they require graphic improvements. However, the effectiveness of these tools has not been practically tested in the field. Therefore, further development must integrate academic validity with classroom trials to ensure its positive impact on student motivation.